The Relationship Between Smartphones Used Before Sleep and Excessive Daytime Sleepiness Among Nursing Students: A Cross-Sectional Study - Ollyvia Freeska Dwi Marta; Arlia Safitri; Nur Aini (University of Muhammadiyah Malang, 2021)
Introduction: Smartphone is a communication device can connecting all distances with many features and always update along time. Smartphone use can’t regardless from all of the student’s activities without knows of the time. Objectives: The aim of the study to explore the relationship between smarthphone used before sleep and excessive daytime sleepiness among nursing students. Methods: We used correlational descriptive with cross sectional approach. Sample of this research was nursing students of the class of 2019th in Faculty of Health Sciences, University of Muhammadiyah Malang. We included 108 respondents, taken by the selection of sample used Convenience Sampling (Accidental Sampling) technique. The data collection used questionnaire with Online Form methods. Spearman Correlation test was used to analyze the data. Results: The result of this research shows that 50.9% the students are excessive smartphone use before sleep’s category and 82.4% had EDS value of normal category. The results of Spearman Correlation test analysis obtained of ρ value = 0.508 higher than the significance level of 0,05, so H1 was rejected.Conclusions: There is no relationship between relationship of smartphone use before sleep and excessive daytime sleepiness in nursing student on University of Muhammadiyah Malang.